Ionic Liquid Co-Catalyst Assisted Biodiesel Production From Waste Cooking Oil Using Heterogeneous Nanocatalyst: Optimization and Characterization - Baskar, Gurunathan; Anita, Nalathamalar T.; Jeehoon, Han; Naveenkumar, Rajendran (Frontiers in Nanotechnology, 2022)
In the present work, the biodiesel was produced from waste cooking oil (WCO) using both heterogenous zinc doped iron catalyst and co-catalyst tetrabutylammonium iodide (TBAI). Initially, the heterogeneous catalyst zinc doped iron catalyst was synthesized and characterised. The functional group in the heterogeneous catalyst was analysed by FTIR, the crystalline nature was studied by XRD and the size of agglomerated nanosphere structure of the doped catalyst was analysed by SEM. The optimization of transesterification parameters like oil to methanol molar ratio, zinc doped iron concentration, TBAI concentration, temperature and time were carried out for the maximum conversion of biodiesel from WCO. At 50 min the maximum biodiesel conversion of 90% was achieved at 55 °C with 12% catalyst, 30% co-catalyst and 1:11 WCO to methanol ratio. The presence of functional groups and the methyl ester composition of the biodiesel from WCO was analyzed by FTIR and GC-MS. The use of zinc doped iron nanocatalyst with tetrabutylammonium iodide (TBAI) reagent shows good catalytic activity for the synthesis of biodiesel from WCO.